Extracorporeal membrane oxygenation–induced fibrinolysis detected by rotational thromboelastometry and treated by oxygenator exchange. (May 2019) - Durila, Miroslav; Smetak, Tomas; Hedvicak, Pavel; Berousek, Jan
Coagulopathy and bleeding is a frequent phenomenon in patients on extracorporeal membrane oxygenation. The cause may be multifactorial and it may change over time. We present a case when bleeding was caused by hyperfibrinolysis induced by oxygenator. The diagnosis was established by comparing thromboelastometry result from blood obtained before and after oxygenator. Hyperfibrinolysis and bleeding could be successfully treated merely by oxygenator exchange.